ABIRATERONE ACETATE LOADED SOLID LIPID NANOPARTICLES FOR IMPROVED ORAL BIOAVAILABILITY: DESIGN OF EXPERIMENTS BASED FORMULATION OPTIMIZATION, IN VITRO, EX-VIVO AND IN VIVO CHARACTERIZATION - KONATHAM, SURESH; PATANGAY, SHASHIKALA (International Journal of Applied Pharmaceutics, 2023)
Objective: Abiraterone acetate (AA), a BCS Class IV drug, demonstrates biopharmaceutical challenges like polymorphism, poor solubility (<0.5 μg/ml), inconsistent permeability, and low oral bioavailability (<10%) (Hence requires a high dose of 1000 mg/day). The current research’s main objective is to improve oral bioavailability by manufacturing AA-loaded solid lipid nanoparticles (AA-SLNs). Methods: SLNs were manufactured using hot homogenization followed by an ultra-sonication method. Initial screening of lipids (Glyceryl monostearate (GMS), Glyceryl Monooleate (GMO)), and surfactants (Tween 80 and Span 20) was done by mixture design. Based on statistical analysis, GMO and Tween 80 were selected for further optimization, and Central composite design (CCD) of experiments were done to optimize the composition using particle size, polydispersity index (PDI), encapsulation efficiency (EE), zeta potential, and cumulative % drug release as responses. Comparative ex-vivo and in vivo evaluations of optimized formulation were done with the pure drug and marketed formulation. Results: Based on the statistical evaluation, GMO-4.4% and Tween 80-3.6% were optimized. Optimized AA-SLNs were found in a spherical shape with size of 286.7±12.6 nm, PDI of 0.138±0.015, EE of 94.0±1.0 %, and zeta potential of-25.0±1.0 mV. Drug release from optimized formulation was extended for 24 h, and ex-vivo permeability was increased by 2.5 and 1.42 times, whereas Relative Oral bioavailability was improved by 6.36 and 1.99 times compared to pure drug and marketed tablets, respectively. Conclusion: The results concluded that AA-SLNs showed increased oral bioavailability compared to the pure drug and marketed formulation. Hence the dose of the formulation can be reduced to achieve the desired therapeutic effect.